2017
DOI: 10.1016/j.ccell.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell-Derived Tnf Triggers Cholangiocellular Tumorigenesis through JNK due to Chronic Mitochondrial Dysfunction and ROS

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a highly malignant, heterogeneous cancer with poor treatment options. We found that mitochondrial dysfunction and oxidative stress trigger a niche favoring cholangiocellular overgrowth and tumorigenesis. Liver damage, reactive oxygen species (ROS) and paracrine tumor necrosis factor (Tnf) from Kupffer cells caused JNK-mediated cholangiocellular proliferation and oncogenic transformation. Anti-oxidant treatment, Kupffer cell depletion, Tnfr1 deletion, or JNK inhibition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 64 publications
(75 reference statements)
1
129
0
1
Order By: Relevance
“…TNF‐α is able to induce more ROS to aggravate mitochondrial dysfunction characterized by lower mitochondrial membrane potential and less ATP production . MitoSOX fluorescence of NPCs was increased in the TNF‐α group compared with the control group, suggesting TNF‐α is capable of aggravating oxidative stress NPCs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…TNF‐α is able to induce more ROS to aggravate mitochondrial dysfunction characterized by lower mitochondrial membrane potential and less ATP production . MitoSOX fluorescence of NPCs was increased in the TNF‐α group compared with the control group, suggesting TNF‐α is capable of aggravating oxidative stress NPCs.…”
Section: Resultsmentioning
confidence: 93%
“…TNF-α is able to induce more ROS to aggravate mitochondrial dysfunction characterized by lower mitochondrial membrane potential and less ATP production. 10,26 MitoSOX fluorescence of NPCs was increased in the TNF-α group compared with the control group, suggesting TNF-α is capable of aggravating oxidative stress NPCs. After pretreatment of PD for 2 hours, the MitoSOX fluorescence decreased significantly compared with the TNF-α group, which indicated PD could facilitate ROS scavenge in NPCs (Figure 4A,B).…”
Section: Pd Prevents Tnf-α-induced Mitochondrial Dysfunction In Ratmentioning
confidence: 90%
“…A recent study ( 12 ) opened a Pandora´s box for therapeutic options targeting the JNK signaling pathway, a major regulator of cell proliferation, against CCA. Earlier, several studies confirmed the critical role of the JNK signaling pathway in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…( 9‐11 ) Importantly, JNK has lineage‐determinant functions in liver parenchymal cells (LPCs) where it not only favors proliferation of biliary cells but also directly biases biliary cell‐fate decisions in bipotential hepatic cells. It has been reported that JNK inhibition delays CCA progression ( 12 ) by impeding JNK‐mediating biliary proliferation. These data indicate that JNK modulation would be of therapeutic benefit in patients with CCA.…”
mentioning
confidence: 99%
“…Recently, a study found that hepatocyte‐specific Hspd1 knockout induced mitochondrial dysfunction, producing excessive ROS and causing cell damage that recruited macrophages to secrete tumor necrosis factor α (TNFα). TNFα/JNK (c‐Jun N‐terminal kinase)/c‐Jun signaling pathway activation promoted the development of hepatocytes with dual differentiation potential into cholangiocarcinoma . This finding indicates the important role of ROS in the development of cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 84%